An-Naẓariyyah Al-Ma’rifiyyah Wa Istikhdāmuhā Fī Ta’līmi Al-Lugah - Muna, Lia Aulial; Ningrum, Yunidar Ayu; Pertiwi, Rizqina Wahyu Laras (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2020)
Cognitive theory is the main stream that makes learning and teaching closer to the realities of human learning, because cognitive theory takes into account the characteristics of learners and the factors that influence learning and the process. Cognitive theory aims to answer the basics that help students prepare and processing information so that this information is relevant which means for them become independent in their learning. This cognitive theory is based on attention to internal cognitive process, namely: attention, perception, acceptance, processing, and information processing. And the applicaton of this cognitive theory in language learning is possible in learning material, learning methods, learning media, teaching methods and so on. In this article the writer shows the application of this cognitive theory in the design of subject in speech skill.